The Effect of Cholesterol-Lowering Beverage Consumption, Low-Fat Diet, and Physical Activity on Cholesterol Levels in the Elderly in Makassar - Megavitry, Rissa (West Science Interdisciplinary Studies, 2025)
This study investigates the effects of cholesterol-lowering beverage consumption, low-fat diet adherence, and physical activity on cholesterol levels among elderly individuals in Makassar. Using a quantitative research design, 150 elderly participants were surveyed using a Likert scale (1-5), and data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results show that cholesterol-lowering beverage consumption, low-fat diet adherence, and physical activity all significantly impact cholesterol levels in the elderly. Physical activity was found to have the strongest effect, followed by cholesterol-lowering beverage consumption and low-fat diet adherence. Additionally, indirect effects were found, where cholesterol-lowering beverages and low-fat diet adherence positively influenced physical activity. These findings suggest that a comprehensive approach, combining dietary modifications and increased physical activity, is essential for managing cholesterol levels and promoting cardiovascular health in older adults. The study emphasizes the importance of integrated health interventions targeting diet and exercise for the elderly population.